Creation and Validation of a Photonumeric Scale to Assess Volume Deficiency in the Infraorbital Region. Issue 5 (May 2017) - Niforos, François; Liew, Steven; Acquilla, Raj; Ogilvie, Patricia; Safa, Marva; Signorini, Massimo; Jones, Derek; Hawthorn, Jan; Collins, Caroline; Kerson, Graeme; Sithamparanathan, Myooran
Abstract : BACKGROUND: The eyes are particularly important aesthetic features of the face and revitalization of the infraorbital region has become a focus of aesthetic treatments. Published infraorbital scales to date have limitations in that they have been descriptive, subjective, or have used computer-generated images. Thus, there is an unmet need for a validated scale based on actual images. OBJECTIVE: To develop a practical photonumeric scale that respects the complex anatomy and age-related changes occurring in the orbital area. METHODS AND MATERIALS: The Allergan Infra-oRbital Scale (AIRS) was developed through a multistep process in collaboration with 16 physicians (plastic surgeons, dermatologists, and aesthetic physicians). Scale development involved both online photographs and live assessments of subjects. Interrater and intrarater reliability was assessed using intraclass correlation coefficients (ICCs). RESULTS: The final AIRS showed intrarater and interrater ICCs of 0.78 to 0.86 and 0.91 to 0.98 for live validation and 0.76 to 0.82 and 0.86 to 0.91 for online validation, respectively, demonstrating robust validity. CONCLUSION: The AIRS can be considered a photonumeric scale that accurately describes volume loss in the infraorbital region. It has been validated and is appropriate for use in research or for everyday clinical use for both live and photographic assessment.